Analysis of the corrosion and leakage causes of the propane dehydrator inlet pipeline in an alkylation unit - Weiqi Lian; Zhiwei Sun; Zhaorong He; Zhihong Duan; Yunrong Lyu (Results in Engineering)
The corrosion and leaking mechanism of the propane dehydrator inlet pipeline in an alkylation unit was studied via analysis of macro-observation, chemical composition, mechanical properties, metallographic, fracture morphologies, EDS and XRD, combining with numerical simulation. The corrosion and thinning of the pipeline from the propane extraction system in the alkylation unit, extending from the propane-water wash mixer to the propane extraction dehydrator, is primarily caused by erosion-corrosion. Under the designed operating pressure and temperature conditions of the pipeline, propane is near or within the two-phase boundary between liquid and gas. At locations where structural discontinuities occur, propane is prone to vaporization, forming a two-phase flow, which leads to erosion-corrosion of the pipe wall. This is the main cause of the corrosion in this pipeline.